The effect of flap advancement on bone graft displacement with or without membrane stabilization – a preclinical study - Wenjie Zhou; Emilio Couso-Queiruga; Emilio A. Cafferata; Ausra Ramanauskaite; Frank Schwarz; Clemens Raabe (BMC Oral Health)
Abstract Background Displacement of bone graft materials following horizontal bone augmentation (HBA) procedures may compromise treatment outcomes, yet the role of flap tension remains unclear. This study aims to assess the effect of varying degrees of flap advancement (FA) and associated flap tension on graft displacement during HBA, as well as the influence of membrane stabilization and soft tissue characteristics. Methods HBA was performed at the bone concavity of the diastema region in pig hemimandibles, corresponding to uncontained defect morphologies. Full-thickness mucoperiosteal flaps were coronally advanced using a single periosteal releasing incision (moderate FA1) or additional scoring (major FA2). Sites were randomized for membrane fixation with two pins or no fixation. Changes in graft material thickness (ΔGMT) were assessed at nine reference levels (L0–L8) before and after wound closure via CBCT. Linear regression models were applied to correlate ΔGMT with the FA, fixation and soft tissue phenotypical characteristics. Results Sixty surgical procedures were categorized into four groups (FA1 - Pins, FA1 + Pins, FA2 - Pins, FA2 + Pins). FA2 achieved greater advancement (9.20 ± 0.55 mm) with lower tension (0.02 ± 0.01 N) than FA1 (4.42 ± 0.67 mm; 0.09 ± 0.02 N). Reduced graft displacement was observed at L0 with a mean ΔGMT of -35.66 ± 30.68% for FA2 versus − 44.99 ± 20.80% for FA1 (p < 0.001). Membrane stabilization did not significantly influence the overall ΔGMTs. Regression analysis revealed a significant correlation between FA and ΔGMT (p = 0.01), independent of the fixation method (p = 0.56), and soft tissue phenotypical characteristics (p > 0.06). Conclusions Greater flap advancement and reduced tension improve graft stability during HBA, while membrane fixation with two pins is insufficient to ensure graft stability in challenging, uncontained defect morphologies.